1996
DOI: 10.1074/jbc.271.45.28052
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B Radiation Acts through the Nitric Oxide and cGMP Signal Transduction Pathway to Stimulate Melanogenesis in Human Melanocytes

Abstract: Ultraviolet B (UVB) radiation is the main physiological stimulus for human skin pigmentation; however, the molecular mechanisms underlying this process are still unclear. Recently, nitric oxide (NO) and cGMP have been involved in mediation of skin erythema induced by UVB. Therefore, we investigated the role of NO and cGMP in UVB-induced melanogenesis. In this study, we demonstrated that UVB stimulation of melanogenesis was mimicked by exogenous NO donors. Additionally, we showed that NO stimulated cGMP synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
144
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(158 citation statements)
references
References 33 publications
(27 reference statements)
10
144
0
4
Order By: Relevance
“…5 Inhibition of melanin synthesis significantly reduces the generation of dark CPDs. Additionally, UV radiation (UVR) activates inducible nitric oxide synthase (iNOS) and NADPH oxidase (NOX), which generate nitric oxide and superoxide, respectively 6,7 (Fig. 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 Inhibition of melanin synthesis significantly reduces the generation of dark CPDs. Additionally, UV radiation (UVR) activates inducible nitric oxide synthase (iNOS) and NADPH oxidase (NOX), which generate nitric oxide and superoxide, respectively 6,7 (Fig. 1).…”
mentioning
confidence: 99%
“…We also observed that UVA is able to solubilize melanin polymer 2 and the resulting melanin derivatives and monomers can diffuse intracellularly, potentially entering the nucleus. In addition, peroxynitrite and nitric oxide can diffuse across membranes and there are reports of NOX4 in the nucleus, 7 which would generate superoxide. This series of events would lead to the generation of dioxetanes on the melanin derivatives in the nucleus.…”
mentioning
confidence: 99%
“…In human melanocytes, NO donors and cGMP analogs stimulate melanogenesis. Furthermore, UV radiation increases both NO and cGMP production, and the effects of UV on melanogenesis can be blocked by guanylate cyclase and NO synthase inhibitors (29). These data strongly suggest that NO and cGMP production are required for UVB-induced melanogenesis.…”
Section: Direct Effects Of Uv On Melanocytesmentioning
confidence: 86%
“…Active PKC then phosphorylates tyrosinase, leading to its activation (Park and Gilchrest, 1999). Recently, there are reports that cGMP signal transduction pathway stimulates melanogenesis (Romero-Graillet et al, 1996;Romero-Graillet et al, 1997). The signal transduction pathway in GR-mediated stimulation of melanogenesis requires further study.…”
Section: Discussionmentioning
confidence: 99%